Peculiarities of heavy metal accumulation in fish from open water bodies and aquarium conditions - Kolomiytseva, Olha; Kolomiitseva, Olga; Kolomiitseva, O.; Kolomiitseva, Olha Mykolaivna; Kolomiitseva, Olha; Коломійцева, Ольга Миколаївна (Гідроекологічне товариство України, 2024)
This research is dedicated to studying the peculiarities of heavy metal accumulation in fish inhabiting open water bodies and in aquarium conditions. The presence of all the studied heavy metals (zinc, copper, lead) was found in the muscles of the silver crucian carp Carassius gibelio. The analysis of the research results indicates that copper and lead levels were within permissible limits, while zinc levels significantly exceeded the standards in both experimental groups (46.5±10.9 and 129.1±69.47 mg/kg). Дослідження присвячене вивченню особливостей накопичення важких металів у риб, які мешкають у відкритих водоймах та в умовах акваріума. Встановлена наявність усіх досліджуємих важких металів (цинк, мідь, свинець) у м’язах карася сріблястого Carassius gibelio. Аналіз результатів дослідження, свідчить, що мідь та свинець знаходились у межах гранично-допустимих концентрацій, цинк значно перевищував норми в обох дослідних групах (46,5±10,9 і 129,1±69,47) мг/кг.
Особливості накопичення важких металів у риб відкритих водойм і в акваріумальних умовах
Коломійцева Ольга Миколаївна http://orcid.org/0000-0002-0697-7715
Keywords: aquarium conditions; акваріумальні умови; heavy metals; важкі метали; zinc; цинк; copper; купрум; lead; плюмбум; crucian carp; карась; natural water bodies; природні водойми